Understanding child psychology - Brain, C. Christine Brain; Mukherji, P. Penny Muherji (Cheltenham : Nelson Thornes, 2005)
This book explores the factors within child psychology that are important when studying the development of children. Suitable for all those working in an early years setting, this highly accessible text covers a wide range of issues from suggestions about how children learn, to how attachments and friendships are formed. The book covers such topics as the development of cognitive processes, language development, emotional development and other aspects that affect a child's development, such as stereotyping and labeling.